THE ROLE of GENERAL PRACTITIONER in PSYCHOTHERAPY of PATIENT BINGE EATING DISORDER - Fajrin, Ria (Journal of Psychiatry Psychology and Behavioral Research, 2024)
Introduction – Binge Eating Disorder (BED) is a condition in which an individual has repeated episodes of binge eating or episode purging type (inducing vomiting by himself or by using laxatives, diuretics, or enemas). It has happened during at last 3 months. The prevalence of binge eating disorder peaks in female adolescents aged 19-22 years and male adolescents aged 24 years. Treatment that can be given for BED includes psychotherapy, pharmacotherapy, and weight loss therapy. Psychotherapy is the first-line treatment for BED. Types of psychotherapy used in BED are Cognitive behavior therapy (CBT), Interpersonal psychotherapy (IPT), and Dialectical behavior therapy (DBT). Methods – The searching method in this article is based on several journals and textbook reviews including diagnosis of BED, and psychotherapy of BED such as Cognitive Behavior Therapy (CBT), Dialectical Behavior Therapy (DBT), and Interpersonal Psychotherapy (IPT). Results – A binge eating disorder (BED) is someone who experiences uncontrollable binge eating, and these episodes can be repeated. after that, someone is trying to get his food out or purging (inducing vomiting by himself or by using laxatives, diuretics, or enemas). This is happened during the last 3 months. Psychotherapy is a formal process that involves the interaction between 2 or more people. Several professionals in mental health use psychotherapy. Types of psychotherapy used in BED are CBT, IPT, and DBT. Discuss – The role of GP in CBT is to help patients change their patterns of thinking and what they do. CBT also helps patients develop their skills to identify, and deal with problematic thoughts, and beliefs The role of a GP in IPT is to help people manage negative feelings so they don't vent those feelings by binge eating. IPT enhances the development of healthy interpersonal skills by replacing maladaptive behavior by promoting a positive self-image. DBT is a complete therapy. it consists of many different components, which include behavior therapy such as exposure therapy, skill in taking an action (contingency), stimulus control skills, problem-solving, cognitive restructuring, and other interventions. Conclusion – The three psychotherapies are interrelated with each other, with the combination of the three therapies on BED the results will be better.    Keywords: BED, CBT IPT, DBT, general practitioner.